2020
DOI: 10.3390/su12125195
|View full text |Cite
|
Sign up to set email alerts
|

KPIs Reporting and Financial Performance in the Transition to Mandatory Disclosure: The Case of Italy

Abstract: European companies of public interest requested to comply with the Directive 2014/95/EU on Non-Financial Information (NFI) are allowed to fulfil the regulatory obligation following the Global Reporting Initiative (GRI) guidelines, which constitute at present the most widely spread framework for sustainability reporting. Given such prevalence, this paper examines the level of disclosure on Key Performance Indicators (KPIs) and its relationship with financial performance over the period 2016–2018 for Italian-lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 143 publications
3
13
0
Order By: Relevance
“…This reduction might be regarded as the need to report only information considered material according to the Decree, leading to the identification of a factor of razionalisation in the new regulation that supports more effective communication with stakeholders Tarquinio et al 2020). This interpretation is consistent with previous research, according to which a lower quantity of information is not associated with a decrease in quality (Crawford and Williams 2010;Loprevite et al 2020). Furthermore, considering the provision of mandatory assurance of NFI, the reduced amount of NFI might suggest a prudent approach to disclosure that induces companies to review the content of their NFI reports Tarquinio et al 2020).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This reduction might be regarded as the need to report only information considered material according to the Decree, leading to the identification of a factor of razionalisation in the new regulation that supports more effective communication with stakeholders Tarquinio et al 2020). This interpretation is consistent with previous research, according to which a lower quantity of information is not associated with a decrease in quality (Crawford and Williams 2010;Loprevite et al 2020). Furthermore, considering the provision of mandatory assurance of NFI, the reduced amount of NFI might suggest a prudent approach to disclosure that induces companies to review the content of their NFI reports Tarquinio et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…In Italy, we detected a progressive reduction in disclosure levels that involved the three indicator categories, especially the economic category. The same trend was found in previous studies that analysed the dynamics in the use of GRI indicators before and after the entry into force of the Italian Decree (Loprevite et al 2020;Tarquinio et al 2020). This reduction might be regarded as the need to report only information considered material according to the Decree, leading to the identification of a factor of razionalisation in the new regulation that supports more effective communication with stakeholders Tarquinio et al 2020).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Non-financial KPIs were found to be used in corporate reporting (Arvidsson, 2011), and what is more, to directly affect the company's social performance and indirectly its bottom line (Lisi, 2018). Similarly, Loprevite et al (2020) identified a positive association between the level of disclosure on KPIs and financial performance. Bradley and Botchway (2018) focused on the use of KPIs in the coffee industry and found a considerable variance in the KPIs disclosed, which led them to the conclusion about the discretionary nature of nonfinancial reporting.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
“…A number of studies and discussions have focused on the potential benefits of such business behaviour compared to the costs of achieving sustainable goals. The most frequently mentioned benefit is the growth of a company's sustainable performance, due to which the company's financial health strengthens [7]. Da Costa and Boente [8] agree with this conclusion, stating that the aim of companies is to include all the basic dimensions of sustainable development and to integrate this concept into corporate governance, precisely in order to increase performance.…”
Section: Introductionmentioning
confidence: 99%